Comparative framing analysis of the 1Malaysia Development Berhad issue in Malaysian mainstream newspapers post Ge-14 - Ahmad, Arman; Ahmad Ghazali, Akmar Hayati; Mohd Zawawi, Julia Wirza; Mohammad Razi, Siti Aishah (Human Resource Management Academic Research Society, 2021)
External factors such as political actors along with journalistic practice influence the news frames, selection of news sources and tone embedded in news. Following the landmark 14th Malaysia General Election, political changes leading to the election also opened opportunities for reform in the Malaysian media landscape. Since the election, there have been calls for local scholars to revisit the new Malaysian media environment and re-evaluate the functions and roles of the media. To answer the question from the perspective of a framing theory framework, this paper will examine the contest for news frames in the coverage of Malaysian mainstream newspapers on the 1MDB scandal, the primary political issue covered in the run-up to GE14. Previous research posits that a winning party will have an edge over and will dominate frames in the media. The main factor for the presence of frames is the power of a political organisation that promotes frames. The idea that the new government will become the major frame setter is also reinforced by the indexing hypothesis. When the news explicitly slants, the politicians supported by the slant gain more influence and are empowered to do whatever they want without fear of being punished by voters. Those who are defeated in the framing competition become weaker, with less freedom to do and say as they please. The focus of this study then will be to understand how, in the aftermath of General Election 14, has Malaysian mainstream media changed in its framing of the 1MDB issue after the loss of the ruling coalition. Specifically, it attempts to understand the relationship that political actors have on news frames, tone and use of sources on the 1MDB issue between the period before and after the 14th General Election, to discover if Malaysian mainstream media has started to evolve beyond the development model.